CHINA'S ROLE IN INTERNATIONAL TRADE AMID DURING IN TRADING ATTACKS WITH THE UNITED STATES - Dewi, Chika (PEOPLE: International Journal of Social Sciences, 2019)
Protectionist policies towards Chinese trade aim to balance US trade with China. The United States has seen the Chinese economy which has expanded into the world and become a new emerging force, even the United States sees the Made in China plan in 2025. Amid during in a trade war with the United States, China must be able to survive to keep the economy stable and also to save Chinese interests. The purpose of this study is to discuss more the role of China in international trade amid during in a trade war between the United States, whether it will decline or continue to be improved because the two countries are trade partners that are interdependent to each other. The research method used is a qualitative method. The result of this research is the fact that China still has a role in international trade amid during in a trade war with the United States. The role was then carried out by China through a counter policy towards the United States and several collaborative supports with several countries. Thus, China's role in international trade did not decrease significantly amid during in a trade war.